1994
DOI: 10.1177/000992289403300301
|View full text |Cite
|
Sign up to set email alerts
|

Physician Beliefs, Attitudes, and Approaches Toward Lyme Disease in an Endemic Area

Abstract: To assess the beliefs and practice habits regarding Lyme disease among practitioners, questionnaires were sent to physicians in a seven-county Lyme-endemic region. One hundred twenty-four evaluable responses were returned from 53 family physicians, 39 pediatricians, 27 internists, and five subspecialists who diagnosed three to four cases of Lyme disease per year, on average. The majority presented with erythema migrans (EM) or other early symptoms, although arthritis was the presenting sign in 16%. The enzyme-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…The IDSA and ILADS Guidelines differ substantially, revealing the wide variation in diagnosis and treatment (TABLE 1) [59,60]. This variation suggests that physicians do not use a uniform strategy to diagnose and treat Lyme disease.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…The IDSA and ILADS Guidelines differ substantially, revealing the wide variation in diagnosis and treatment (TABLE 1) [59,60]. This variation suggests that physicians do not use a uniform strategy to diagnose and treat Lyme disease.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…Previous surveys focused on LD and were conducted in LD-endemic states (Eppes et al, 1994; Magri et al, 2002; Murray and Feder, 2001; Strickland et al, 1994). The goals were to determine how commonly providers see patients with tick-borne diseases, what they know about diagnosis and management of selected diseases, what their practices are with regard to post-tick bite prophylaxis, and where they obtain information regarding tick-borne diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the fact that all nurses share similar training, sit for the same licensure exams, and attend the same in-service training programs contributed to these results. Eppes et al (1994) assessed physicians' knowledge of LD and found similar understanding of LD among different medical specialties. Interestingly, our study concluded that length of service with LHD was not a factor in LD knowledge.…”
Section: Discussionmentioning
confidence: 94%
“…This is understandable when one considers the difficulties that physicians and laboratories have in consistently and accurately diagLyme Disease 9 nosing LD cases. For example, Eppes et al (1994) showed physicians were lacking knowledge about the confirmatory laboratory test for LD. Vogt's (1992) study showed inconsistencies among states in types of confirmatory laboratory testing done for LD.…”
Section: Discussionmentioning
confidence: 99%